PENGARUH JENIS PELARUT TERHADAP RENDEMAN, KANDUNGAN FLAVONOID TOTAL, DAN SAPONIN EKSTRAK DAUN SIRIH HIJAU (Piper betle L.) MENGGUNAKAN METODE SOKLETASI - lutfiyatul mukhlisah; Erina Endah Kusuma Wardani; Daning Kinanti Sutama; Maghfiroh Maghfiroh (Universitas Samudra, 2026)
Green betel leaves (Piper betle L.) contain secondary metabolite compounds such as flavonoids and saponins, which have potential as antioxidants and antimicrobials. The choice of solvent type affects the effectiveness of extracting these compounds. This study aimed to determine the effect of solvent type on the extraction results of flavonoids and saponins from green betel leaves using the soxhletation method. Extraction was carried out using 25 grams of sample at a temperature of 60–90°C for 4 hours with three types of solvents, namely 96% ethanol, ethyl acetate, and n-hexane. Each treatment was performed in triplicate. The obtained extracts were tested for flavonoid and saponin content qualitatively, and total flavonoid levels were determined using UV-Vis spectrophotometry. The results showed that ethanol gave the highest flavonoid intensity (++++), followed by ethyl acetate (+++) and n-hexane (+). The saponin test showed positive results for ethanol and n-hexane, while ethyl acetate yielded negative results. The highest total flavonoid content was obtained with ethyl acetate at 637.1 mg QE/g, followed by 96% ethanol at 631.7 mg QE/g, and n-hexane at 243.4 mg QE/g. Based on these results, ethyl acetate was the most effective solvent for extracting total flavonoids, while 96% ethanol was able to extract both flavonoids and saponins more broadly.